Real 3D play of final fantasy : next generation RPG game - Lim, Ivy Qiu Ling (2016)
In the modern days now, many countries are transforming into smart cities, almost everyone owns a mobile phone or mobile gadgets. As technologies advances, mobile gadgets are improving and more advance features are added in. Comparing to the old modern mobile that people used in the olden days which can only make calls, mobile phone nowadays can not only make calls, it is able to even communicate through internet networks and Bluetooth. With the new functionality, people, designers and developer are able to make used of the different functions and design many different application to serve the user. The main purpose of this project report is to allow people to understand more about Bluetooth beacon and the platform, which was used to build the android application. This report consist of two main parts which is the knowledge of the equipment that was used and the development of the mobile application. The goal of the project is to make use of the Bluetooth function which is available in almost all the mobile nowadays, and implement it with Bluetooth beacon in order to make the mobile application more interactive rather than just having an application, which cannot react and interact with the user. This project is about having an application that provides interaction of mobile and the real world. Therefore, the application would be design in a way that when mobile detected or sense the beacon, it will react according.